Modification of Poly(Glycerol Adipate) with Tocopherol and Cholesterol Modulating Nanoparticle Self-Assemblies and Cellular Responses of Triple-Negative Breast Cancer Cells to SN-38 Delivery - Jiraphong Suksiriworapong; Chittin Achayawat; Phutthikom Juangrattanakamjorn; Vincenzo Taresco; Valentina Cuzzucoli Crucitti; Krisada Sakchaisri; Somnuk Bunsupa (MDPI AG, 2023)
This study aimed to fabricate new variations of glycerol-based polyesters by grafting poly(glycerol adipate) (PGA) with hydrophobic bioactive moieties, tocopherol (TOC), and cholesterol (CHO). Their effects on nanoparticle (NP) formation, drug release, and cellular responses in cancer and normal cells were evaluated. CHO and TOC were successfully grafted onto PGA backbones with 30% and 50% mole grafting. Increasing the percentage of mole grafting in both molecules increased the glass transition temperature and water contact angle of the final polymers but decreased the critical micelle concentration of the formulated particles. PGA-TOC NPs reduced the proliferation of MDA-MB-231 cancer cells. However, they enhanced the proliferation of primary dermal fibroblasts within a specific concentration range. PGA-CHO NPs minimally affected the growth of cancer and normal cells. Both types of NPs did not affect apoptosis or the cell cycle of cancer cells. PGA-CHO and PGA-TOC NPs were able to entrap SN-38, a hydrophobic anticancer drug, with a particle size <200 nm. PGA-CHO NPs had a higher drug loading capacity and a greater drug release than PGA-TOC NPs. However, SN-38-loaded PGA-TOC NPs showed higher toxicity than SN-38 and SN-38-loaded PGA-CHO NPs due to the combined effects of antiproliferation and higher cellular uptake. Compared with SN-38, the drug-loaded NPs more profoundly induced sub-G1 in the cell cycle analysis and apoptosis of cancer cells in a similar pattern. Therefore, PGA-CHO and PGA-TOC polymers have potential applications as delivery systems for anticancer drugs.